2012
DOI: 10.1007/s00408-012-9427-3
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Syndrome: Blood Viscosity, Blood Coagulation Abnormalities, and Early Atherosclerosis

Abstract: Obstructive sleep apnea syndrome (OSAS) is an independent risk factor for atherosclerosis and arterial thrombosis, which are associated with high cardiovascular (CV) morbidity and mortality. In studies performed in clinical populations with elevated CV event risk profiles, the occurrence of moderate to severe OSAS was very often accompanied by a worsened vascular function and increased prevalence of structural abnormalities. Recent investigations of atherosclerosis in OSAS have focused on thrombotic tendency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 45 publications
1
36
1
3
Order By: Relevance
“…Atherosclerosis is common in OSAS, and several studies have demonstrated that the elevated mortality in OSAS is associated with the severity of the atherosclerosis [33]. In OSAS subjects the carotid intima-media thickness is significantly increased compared to controls [22] and a recent study has demonstrated that OSAS severity is correlated also with subclinical coronary atherosclerosis [38].…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis is common in OSAS, and several studies have demonstrated that the elevated mortality in OSAS is associated with the severity of the atherosclerosis [33]. In OSAS subjects the carotid intima-media thickness is significantly increased compared to controls [22] and a recent study has demonstrated that OSAS severity is correlated also with subclinical coronary atherosclerosis [38].…”
Section: Introductionmentioning
confidence: 99%
“…COX-1 inhibition reduced lesion progression in intermittent hypoxia mice. This study has demonstrated, for the first time, that the activation of the COX pathway exposed to CIH is associated with increased atherosclerotic lesions in mice, highlighting early atherosclerosis markers in OSA patients [1,2].…”
Section: Descriptionmentioning
confidence: 66%
“…COX-1 inhibition reduced lesion progression in intermittent hypoxia mice. This study has demonstrated, for the first time, that the activation of the COX pathway exposed to CIH is associated with increased atherosclerotic lesions in mice, highlighting early atherosclerosis markers in OSA patients [1,2].CIH and sleep disruption are responsible of pathophysiological pathways determining a systemic disease. In fact, OSA has been associated with diseases with a high inflammatory potential, such as psoriasis and other autoimmune disorders.…”
mentioning
confidence: 70%
“…41 In addition, research has emphasized that thrombotic tendency and blood viscosity are possible mechanisms of disease in subjects with OSA and cardiovascular comorbidity. 2 …”
Section: Possible Mechanism Of Cpap On Blood Pressurementioning
confidence: 99%
“…1 It is known that OSA is a considerable risk factor for both cardiovascular and cerebrovascular diseases. 2 CPAP treatment is the standard for managing OSA and has been proven to reduce the apnea-hypopnea index (AHI), improve sleep quality in subjects with OSA, 3 and decrease the risk for cardiovascular comorbidities. 4 An increase in blood pressure has a high correlation with OSA, and CPAP lowers the mortality rate in subjects with severe OSA.…”
Section: Introductionmentioning
confidence: 99%